PSYCHOLOGICAL ASPECTS OF ARCHITECTURAL SPACE PERCEPTION - Demydiuk, Oksana; Averbakh, Mykhaylo (Sworld-Us Conference proceedings, 2023)
The article updates aspects of the psychological impact of the architectural environment on human feelings and behavior. Methods of architectural objects and spaces evaluation by the consumer are revealed. Attention is focused on the real urban space, in